1997
DOI: 10.1021/bi971408k
|View full text |Cite
|
Sign up to set email alerts
|

RNA Recognition by a Bent α-Helix Regulates Transcriptional Antitermination in Phage λ

Abstract: A novel RNA recognition motif is characterized in an arginine-rich peptide. The motif, derived from lambda transcriptional antitermination protein N, regulates an RNA-directed genetic switch. Its characterization by multidimensional nuclear magnetic resonance (NMR) demonstrates specific RNA-dependent folding of N- and C-terminal recognition helices separated by a central bend. The biological importance of the bent alpha-helix is demonstrated by mutagenesis: binding is blocked by substitutions in the N peptide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
93
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(99 citation statements)
references
References 56 publications
6
93
0
Order By: Relevance
“…The two labeling positions were chosen based on previous studies to minimize potential disruptions to the native conformation(s) of the N-peptide/boxB complex (Su et al 1997). In the NMR structure of the N-peptide/boxB complex, side chains of these two positions point away from the peptide/RNA interface ( Fig.…”
Section: Experimental Design and Biochemical Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…The two labeling positions were chosen based on previous studies to minimize potential disruptions to the native conformation(s) of the N-peptide/boxB complex (Su et al 1997). In the NMR structure of the N-peptide/boxB complex, side chains of these two positions point away from the peptide/RNA interface ( Fig.…”
Section: Experimental Design and Biochemical Characterizationmentioning
confidence: 99%
“…Circular dichroism (CD) measurements indicated that the N-peptide is disordered and only folds when bound to boxB RNA . NMR studies (Su et al 1997;Legault et al 1998;Schärpf et al 2000) revealed that in the bacteriophage l N-peptide/boxB complex, N-peptide adopts a bent a-helical conformation, while the boxB pentaloop (G6A7A8A9A10) folds into a stable GNRA tetraloop with the fourth loop base (A9) extruded out (Fig. 1A,D,E).…”
Section: Introductionmentioning
confidence: 99%
“…The methyl group of Ala13 lies between C7 and C8, packing against both the ribose and base H5/H6 protons of these nucleotides. This alanine is conserved among the family of N proteins, and mutagenesis of this position in the N system showed that only alanine and serine maintained wild-type binding affinity for the boxB RNA (Su et al 1997). Tyrosine-17 is one turn up the ␣-helix and lies between U9 and C10, the next two bases up the stem from the Ala13 position.…”
Section: Van Der Waals Contactsmentioning
confidence: 99%
“…The N peptide has a pronounced bend in the ␣-helix of ∼120°as a result of deviations of the backbone and angles for Arg11. This bend has been shown to be important for N binding (Tan and Frankel 1995;Su et al 1997) and antitermination in vivo (Franklin 1993;Su et al 1997), and is required for bringing Trp18 into position for stacking onto the boxB tetraloop. The N P22 peptide ␣-helix is also bent, peptide ␣-helix is almost linear.…”
Section: Overview Of 21 and P22 N Peptide-boxb Structuresmentioning
confidence: 99%
“…NMR structural studies (10)(11)(12) demonstrated that the amino terminal of the N protein (N peptide), which features an arginine-rich motif, binds to the boxB RNA hairpin as a bent ␣-helix, and this process enforces the purine-rich boxB RNA pentaloop to adopt a canonical GNRA fold (13,14) with the fourth purine residue extruded (Fig. 1).…”
mentioning
confidence: 99%